Molecular mechanism of NO-induced cell death of PC12 cells by IFN gamma and TNF alpha - Yi, Seh Yoon; Han, Seon Kyu; Lee, Jee Yeon; Yoo, Young Sook (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2005)
Nitric oxide (NO) is a small, diffusible, and highly reactive molecule, which plays dichotomous regulatory roles under physiological and pathological conditions. NO promotes apoptosis in some cells, and inhibits apoptosis in other cells. In the present study, we attempted to characterize the NO signaling pathway and cellular response in PC12 cells treated with cytolkines. IFN-gamma/TNF-alpha treatment resulted in a synergistic increase of nitrite accumulation, with the induction of inducible nitric oxide synthase (NOS) in the PC12 cells. Moreover, as nitrite concentration increased, cell viability decreased. In order to explore MAP kinase involvement in nitric oxide production resultant from IFN-gamma/TNF-alpha stimulation, we measured the activation of MAP kinase using specific MAP kinase inhibitors. PC12 cells pretreated with SB203580, a p38 MAP kinase-specific inhibitor, resulted in the inhibition of iNOS expression and NO production. However, PD98059, an ERK/MAP kinase-specific inhibitor, was not observed to exert such an effect. In addition, Stat1 activated by IFN-gamma/TNF-alpha was interacted with p38 MAPK. These data suggest that p38 MAP kinase mediates cytokine-mediated NOS expression in the PC12 cells, and Jak/Stat pathway interferes with p38 MAPK signaling pathway.
Keywords: NITRIC-OXIDE SYNTHASE; ACTIVATED PROTEIN-KINASE; NECROSIS-FACTOR-ALPHA; INDUCED APOPTOSIS; EXPRESSION; MACROPHAGES; INVOLVEMENT; OVEREXPRESSION; INHIBITION; ASTROCYTES